Identifying Social Commerce Features towards Improving a Social Commerce Website - et.al, Norshaharizan Puteh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Social commerce has become more popular compared to e-commerce. This is caused by the transition development of the business transaction website. It has shifted from the e-commerce website towards the social commerce website. The e-commerce website has its standard features. However, there are few features in the market for the social commerce website. This research focuses on investigating the essential functions of social commerce that should be embedded into the social commerce website. The process of identifying social commerce features is done through literature reviewand summarized the features. The summarized characteristics than are analyzed and discussed with three expert reviewers to conform to the relevant social commerce features. At this phase, it involves several steps where the discussion started with an individual interview. The outcome then is consolidated into a table. The reviewed then be emailed to expert reviewers to get their feedback. The agreement from all of them then be gathered and summarized in a new set of features. The outcome of thisstudy will be useful for the development of a design template for a social commerce website.